Proliferation and Differentiation of Human Hair Follicle Stem Cells on Chitosan-Skin Engineered Template in Vitro - Abu Bakar, Mohd Hilmi; Mohd Noor, Norhayati; Ahmad Sukari, Halim; Zulkifli, Mustafa; Zamzuri , Idris; Saidi, Jaafar (Indonesian Society for Knowledge and Human Development, 2017)
Hair follicles repeatedly regress and reconstitute themselves, suggesting the presence of intrinsic tissue stem cells. Among the unique characteristics of adult stem cells isolated from hair follicles is their ability to differentiate into keratinocytes. Study on chitosan skin-engineered templates (SETs) as scaffolds for the proliferation of human fibroblasts have shown the promise of SETs in facilitating skin cell growth in three-dimensional culture. High proliferation in three-dimensional culture using human cells allows the researcher to extensively evaluate the cultivation of desirable cell types on chitosan SETs. Therefore, this study aimed to evaluate the in vitro attachment, proliferation and differentiation of hair follicle stem cells (HFSCs) on a chitosan SETs. HFSCs were isolated from human scalp tissues using collagenase type I prior to propagation in supplemented CnT-07 media. The phenotype of the HFSCs was verified using the markers keratin-15 (K15) and CD200, as detected by immunocytochemical staining. The attachment and proliferation of the HFSCs on the chitosan SETs were evaluated using scanning electron microscopy (SEM), an alamar blue assay and a live/dead assay. Subsequently, the HFSCs were differentiated using CnT-2D differentiation media. The cells’ differentiation was verified using the markers involucrin and keratin-6 (K6), as detected by immunofluorescence staining. The HFSCs were successfully isolated, proliferated and differentiated according to staining positivity and microscopy imaging. HFSCs are able to proliferate and directly differentiate into keratinocytes on a chitosan SETs, which may facilitate their use in regenerative medicine.